Basic Skills, Literacy Practices and the 'Hidden Injuries of Class'. (February 2015) - Cieslik, Mark; Simpson, Donald
This paper draws on qualitative data from three research projects that examined the impact of poor skills on the life chances of adults living in two disadvantaged areas of England. We employed the theories of Goffman and Bourdieu to document how problems with literacy have a corrosive effect on the identities of interviewees, threatening their wellbeing. Though learning difficulties occur across all social backgrounds, the poor family resources and educational opportunities of our respondents meant they struggled to overcome their literacy problems when young, thus shaping later life course transitions. Thus the origins of the shame that our adults felt about their poor skills lie in part in the distinctive classed experiences they had when young. However, the resourcefulness of our respondents meant that many had secured employment, bought homes and become parents which obscured the ongoing psychic problems that a lifetime of poor skills had bestowed on our sample. The disjuncture between the apparent material standing of our sample and the 'hidden injuries of class' raises questions about how we understand the operation of class across the life course and the role of literacy, learning and wellbeing in the shaping of social identities.